(untitled) (Research, Society and Development, 2021)
Objective: To identify the purpose of digital media use among older adults during the Covid-19 pandemic. Methodology: The indexed literature published in English, Spanish and Portuguese will be systematically searched on 7 databases; the references of studies included will be searched manually. Two authors will independently evaluate titles, abstracts and full-texts according to eligibility criteria. A customized data extraction form will be used to chart the data extracted from the studies. For consideration, studies must be in English, Portuguese or Spanish; involve older adults aged ≥ 55 years (or mean age 60 years); assess older adults who used digital media during the Covid-19 pandemic; be empirical studies with qualitative or quantitative data, have crosssectional or longitudinal design, be letters to the Editor and editorials, and be published between the end of 2019 and 2021. Results: Results will be charted in a table and accompanied by a narrative summary.